Characterization of persistent organic pollutants and culturable and non-culturable bacterial communities in pulp and paper sludge after secondary treatment. (May 2022) - Tripathi, Sonam; Yadav, Sangeeta; Purchase, Diane; Singh, Kaman; AL-Shwaiman, Hind A.; Chandra, Ram
Abstract: Due to the presence of various organic contaminants, improper disposal of pulp-paper wastewater poses harm to the environment and human health. In this work, pulp-paper sludge (PPS) after secondary treatment were collected from M/s Century Pulp-paper Mills in India, the chemical nature of the organic pollutants was determined after solvent extraction. All the isolates were able to produce lipase (6.34–3.93 U ml −1 ) which could account for the different fatty acids detected in the PPS. The dominant strains were in the classes of α and γ Proteobacteria followed by Firmicutes. The Shannon-Weiner diversity indexes for phylotype richness for the culturable and non-culturable bacterial community were 2.01 and 3.01, respectively, indicating the non-culturable bacterial strains has higher species richness and diversity compared to the culturable bacterial strains. However, the culturable strains had higher species evenness (0.94 vs 0.90). Results suggested only a few isolated strains were resistant to the POPs in the PPS, where as non-cultural bacteria survived by entering viable but non-cultural state. The isolated strains ( Brevundimonas diminuta, Aeromonas punctata, Enterobacter hormaechei, Citrobacter braakii, Bacillus pumilus and Brevundimonas terrae ) are known for their multidrug resistance but their tolerance to POPs have not previously been reported and deserved further investigation. The findings of this research established the presence of POPs which influence the microbial population. Tertiary treatment is recommended prior to the safe disposal of pulp paper mill waste into the environment. Highlights: Persistent Organic Pollutants (POPs) were major pollutants in pulp-paper sludge. Six culturable and 40 viable but non-culturable bacterial strains were detected. The resistance to POPs by the culturable bacteria have not been previously reported. The remaining strains survived by entering viable but non-culturable state. The non-culturable bacterial strains has higher species richness and diversity.